A two-step method for damage identification in beam structures based on influence line difference and acceleration data. (July 2018) - Tan, D; Lu, ZR; Liu, JK
This article presents a two-step approach for structural damage identification in beam structure. Damages are located using the influence line difference before and after damage, the calculation of damage severity is accomplished by acceleration data and bird mating optimizer algorithm. Local damages are simulated as the reduction of both the elemental Young's modulus and mass of the beam. The technique for damage localization based on displacement influence line difference and its derivatives for beam structure has been outlined. An objective function that comprises dynamic acceleration is utilized in bird mating optimizer. All data are originated from only a few measurement points. Two numerical examples, namely, a simply supported beam and a four-span continuous beam, are investigated in this article. Identification results from different objective functions are compared with results from objective function conventional modal assurance criterion, which shows the superiority of the proposed function. In addition, results of dynamic responses under different types of excitation are presented. The effect of measurement noise level on damage identification results is studied. Studies in the article indicate that the proposed method is efficient and robust for identifying damages in beam structures.